Wire and arc additive manufacture of tungsten and tantalum - Marinelli, Gianrocco (Cranfield University, 2018)
The advent of the next industrial revolution is clearly represented by the constant maturation of additive manufacturing. Wire + Arc Additive Manufacturing (WAAM) is a novel technique suitable for the deposition of medium to large scale components. This study was focused on investigating the WAAM process for the deposition of refractory metals, such as tungsten and tantalum. Generally, this class of metals is characterised by intrinsic low-temperature brittleness, poor weldability and a high susceptibility to oxidation over a large temperature range. For unalloyed tungsten, the process parameters to produce defect-free autogenous welds were found by varying the shielding gas composition and the welding speed. This represents a fundamental study for the WAAM deposition of tungsten, which has been reported to be markedly influenced by the wire feeding orientation. In particular, wire side feeding produced a large amount of spatter which resulted in an enhanced presence of structural defects within the structure deposited. The occurrence of defects was eliminated when employing wire front feeding. The characteristic microstructure of tungsten was investigated resulting to be composed of two specular arrays of large columnar grains meeting at the centre of the structure. The thermal conductivity and thermal diffusivity of as-deposited and annealed tungsten structures were observed to considerably decrease over the temperature range analysed. 200-mm-long structures in pure tantalum have been also deposited using two wires with different oxygen content. The tantalum structures can be deposited with high integrity and excellent mechanical properties. Superior yield strength was achieved for the WAAM deposited material compared to commercially available tantalum, even though the grains in the WAAM material were larger and had a high aspect ratio. The typical columnar grains of the tantalum deposits were refined into an equiaxed microstructure when additional cold-working was implemented to the deposition process. This led to obtaining a microstructure with an average grain size of 650 μm and completely random texture. Furthermore, two functionally graded structures were produced within the same built using tantalum, molybdenum and tungsten achieving a regular compositional and hardness gradient. The results of this study have shown that WAAM is able to produce refractory metal components with relatively low cost, exploiting the characteristic freedom of 3D printing and the opportunity of obtaining optimised properties, offering a solid alternative manufacture route to powder metallurgy.